AN UPDATED SIMPLIFIED SEVERITY SCALE FOR AGE-RELATED MACULAR DEGENERATION INCORPORATING RETICULAR PSEUDODRUSEN - EJAZ , S; AFTAB, A; LODHI , Y; TARIQ , S; SHAFI , M; BAIG , L (Biological and Clinical Sciences Research Journal, 2024)
Age-related macular degeneration (AMD) is a progressive retinal disease that primarily affects older adults and is one of the leading causes of vision loss worldwide. Objective: This study aims to develop and validate an updated AMD severity scale that includes RPDs, evaluating its ability to predict disease progression. Methods: This cross-sectional study was conducted at Wah Medical College, Wah Catt A total of 155 patients were included in the study. Data from retinal imaging, visual acuity, and OCT measurements were collected and analyzed to classify patients according to the proposed AMD severity scale. Two independent retina specialists, who were blinded to the clinical outcomes, performed the grading of all imaging data. Results: A total of 155 patients with a mean age of 74.2 ± 8.5 years (range 50-92). The cohort comprised 45.2% males and 54.8% females, with 25.8% reporting a history of smoking. The mean baseline visual acuity (VA) was 0.33 logMAR (approximately 20/40). None of the patients in Stage 1 (early AMD) had RPDs, while 44.6% of patients in Stage 2 (intermediate AMD) presented with RPDs. In Stage 3 (advanced dry AMD), 57.1% of patients had RPDs, and the highest prevalence was observed in Stage 4 (wet AMD), where 66.7% of patients were affected. Conclusion: It is concluded that the updated simplified severity scale for age-related macular degeneration (AMD), which incorporates the presence of reticular pseudodrusen (RPDs), provides a more accurate and comprehensive assessment of disease severity and progression.